Real or virtual walkway in luxury fashion context?: A qualitative approach - Aleem, A. K.; Loureiro, S. M. C. (2021 Global Fashion Marketing Conference, 2021)
A qualitative study was conducted with the aim of analyzing luxury brands adaptation concerning the Covid-19 impact on the luxury sector. To this end, luxury brand managers from Lisbon were interviewed as a means to collect insights. Our findings indicate that virtual reality was crucial during the pandemic, as stores were closed, and brands needed to sustain their relationships. Managers enhanced social media as a powerful tool as well.